Expectation and Satisfaction with Nursing Care among Hypertensives Receiving Care at a Resource-Constrained Hospital in Ghana - Kennedy Dodam Konlan; Mavis Armah-Mensah; Rita Aryee; Theresa Akua Appiah (Nursing Research and Practice)
Background. Hypertension accounts for a third of the global preventable premature deaths. In Sub-Saharan Africa, hypertension is the most rapidly increasing cardiovascular disease (CVD) and the second leading cause of death. Proper management of hypertension requires adherence to management by patients and this is partly possible if patients feel satisfied with the nursing care they receive. Satisfaction with nursing care is only possible if there is a congruence between the expectations of care and the actual care received from nurses. Aim. We explored the expectations and satisfaction of Ghanaian hypertensives with nursing care received at the Korle-Bu Teaching Hospital (KBTH). Methods. In this qualitative study, a phenomenological approach was used to gather data about the lived experiences of patients with hypertension about nursing care. In-depth interviews (IDIs) were conducted among sixteen (16) patients with hypertension from the hypertensive Out-Patient Department (OPD) Clinics of the Medical Department at the KBTH. Only patients with history of previous admission(s) at the KBTH during the immediate past six months were purposively recruited. The respondents were interviewed about the nursing care received during their immediate past admission(s) at the KBTH using an IDI-guide. The IDIs were recorded digitally, transcribed verbatim, and reviewed severally and thematic analysis was done. Nvivo 11 software was used to manage the data and aid with the thematic analysis. Results. The results of this study showed that Ghanaian hypertensive patients perceived nurses as key players in the management of patients. On the respondents’ expectations from nurses prior to their immediate past admissions at the KBTH, the data revealed the responsiveness of nurses to patient needs, prompt pain management, high confidentiality level of nurses, rendering of efficient health education, maintenance of therapeutic work environment, and ensuring effective communication as well as professional/ethical practice from the nurses. On the question of what made nursing care satisfying, it was observed from the respondents that they considered the competence of nurses, maintenance of therapeutic environment, and also effective handling of confidential information as determinants of their satisfaction with nursing care. Further, the respondents identified some key areas of dissatisfaction and these included the responsiveness of nurses to patient needs, prompt pain management, effectiveness of health education, and provision of culturally sensitive communication. Disproportionate distribution of nursing staff across the three nursing shifts, unethical practice among some nurses, inadequate resources for work, and low work morale of some nurses were identified as factors responsible for the gaps between patient expectations and actual care received. Conclusion. Our study concludes that continuous professional development programs for nurses should focus on the areas of dissatisfaction so as to improve care for hypertensives. We also recommend that nursing staff distribution across the various shifts should be of keen interest to nurse managers if hypertension care in particular and overall patient care in general are to improve.